2020
DOI: 10.1186/s13104-020-4929-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and optimization of protein extraction and two-dimensional gel electrophoresis protocols for liverworts

Abstract: Objective: Liverworts possess historical adaptive strategies for abiotic stresses because they were the first plants that shifted from water to land. Proteomics is a state-of-the-art technique that can capture snapshots of events occurring at the protein level in many organisms. Herein, we highlight the comparison and optimization of an effective protein extraction and precipitation protocol for two-dimensional gel electrophoresis (2-DE) of liverworts. Results:We compared three different protein extraction met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…As with peanut, the TCA/acetone extract of walnut samples showed a low protein density in terms of composition compared to SDS, PVPP or Ambi/urea extracts. Similar results were obtained by Yadav et al [ 27 ] who found that after precipitation in 20% TCA-acetone, the amount of soluble protein was lower than in 50 mM Tris-HCl (pH 7.5) and 1.5 M Tris-HCl (pH 8.8) solutions. In contrast, when testing different extraction methods for tomato pollen proteome analysis, Sheoran et al [ 47 ] found the TCA-acetone protein extraction method to be more appropriate.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As with peanut, the TCA/acetone extract of walnut samples showed a low protein density in terms of composition compared to SDS, PVPP or Ambi/urea extracts. Similar results were obtained by Yadav et al [ 27 ] who found that after precipitation in 20% TCA-acetone, the amount of soluble protein was lower than in 50 mM Tris-HCl (pH 7.5) and 1.5 M Tris-HCl (pH 8.8) solutions. In contrast, when testing different extraction methods for tomato pollen proteome analysis, Sheoran et al [ 47 ] found the TCA-acetone protein extraction method to be more appropriate.…”
Section: Resultssupporting
confidence: 90%
“…It is therefore usually essential to remove such compounds prior to the analysis, making the procedure more challenging. The standard and primary protocols generally used for protein extraction from plant tissues are the conventional buffer extraction such as ammonium bicarbonate, Tris-HCl, and sodium phosphate [ 27 , 28 ], TCA precipitation [ 29 , 30 , 31 , 32 ], phenol extraction methods [ 33 , 34 , 35 ], polyvinylpolypyrrolidone (PVPP) extraction [ 27 , 28 , 36 ], or using the sodium dodecyl sulfate (SDS) buffer [ 33 , 37 , 38 ]. Doellinger et al [ 39 ] presented a sample preparation method by easy extraction and digestion (SPEED) using neither detergents nor chaotropic agents but pure trifluoroacetic acid for protein extraction.…”
Section: Introductionmentioning
confidence: 99%